16P Neutrophil-lymphocyte ratio as a prognostic marker in a resource constraint setting for metastatic malignancies treated with immune checkpoint inhibitors. (15th December 2019) - Murthy, N Y; Rauthan, A; Patil, P; Somashekhar, S P; Zaveri, S; Lahkar, K; Gupta, K; Nigade, G R; Sood, T; Kulkarni, S S
Abstract: Background: There exists a need for a prognostic marker apart from PDL1 expression for patients being treated with immunotherapy. Neutrophil lymphocyte ratio (NLR) has been shown to correlate with outcomes in certain malignancies treated with immune checkpoint inhibitors (ICI). Methods: A retrospective analysis was carried out of a total of 70 patients who received ICI for metastatic renal cell carcinoma (mRCC) and metastatic non-small cell lung cancer (mNSCLC) from 2016-2019. Peripheral blood NLR of 5 at baseline was used as cut off to divide patients into two groups. Objective response rate (ORR) and overall survival (OS) were calculated in the two groups. Results: 37 patients of mRCC and 33 patients of mNSCLC were treated with ICI. Among the 37 with mRCC, 24 patients (64.9%) had a NLR less than 5. Those with NLR<5 had a significantly better response rate with a ORR of 70.8% as compared to ORR of 15.4% in NLR>5 group (p = 0.01).There was also a marked significant difference in the survival between the two groups with median OS not reached in NLR<5 group v/s 5 months in NLR>5 group( HR = 0.12, 95% CI : 0.04-0.40, p = 0.00). Three patients with NLR< 5 have a ongoing complete response of 40, 38, and 30 months respectively. Among the 33 patients of mNSCLC, 19 patients (57.5%) had NLR of < 5 . Those with NLR<5 had a better response with ORR of 57.9% as compared to 28.5% in NLR>5 . Those with NLR<5 also had a better survival with median OS of 24 months as compared to only 6 months in those with NLR >5 (HR = 0.59). Conclusion: Patients with low NLR had a significantly better response rate and overall survival. In a resource and cost constraint setting, a simple inexpensive test such as NLR would not only be prognostic, but can help in choosing treatment strategies in scenarios where PDL-1 expression does not carry any implication such as in 2 nd line mRCC and 2 nd line mNSCLC. Also with the advent of combination regimens in 1 st line setting (chemo+ ICI in mNSCLC and oral TKI+ICI in mRCC), large scale studies need to be done on whether those with low NLR can benefit with only single agent ICI which would have an impact in not only lowering the cost burden in a developing country such as India but also maintain a better quality of life. Legal entity responsible for the study: Nitin Yashas Murthy. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.